How does security limit the right to protest? : a study examining the securitised response to protest in South Africa - Royeppen, Andrea Leigh (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2014)
In South Africa, the right to protest is under constant threat as a result of the state response. Increasing cases of forceful policing and sometimes unlawful procedural prohibitions of protest attest to this. This study aims to firstly describe this situation through securitisation theory, essentially arguing that South Africa has become a securitised state. It also aims to understand how this is sustained by the state and why the state needs to use a securitised response to maintain power. Interviews were conducted with members of different communities and organisations. Their responses helped to illustrate the frustration of the right to protest or brutal policing during a protest. This provided primary evidence to support the claims of the study. The research shows that claims to protest are being delegitimised under the guise of security as protestors are being constructed as threats to the state. This is further substantiated by looking at how the reorganisation and remililtarisation of the South African Police perpetuates the criminalisation of protestors which necessitates a forceful response from the state. Furthermore, it shows that there is a distinct relationship between the prohibition of protest and the recent increase in 'violent' protests which legitimate forceful policing thereby creating a state sustained cycle of violence. The larger implication of this treatment is that these protestors are treated as non- citizens who are definitively excluded from participating in governance. In understanding why this is taking place, it is clear that a securtitised response is an attempt to maintain power by dispelling any threats to power, a response which is seen to have a long history in the African National Congress (ANC) when examining the politics of the ANC during exile. Maintaining power in this way distracts from the larger agenda of the state, which this thesis argues, is to mask the unraveling of the ANC's hegemony and inability to maintain national unity. In other words, the increasing dissatisfaction of some of the citizenry which has manifested through protest greatly undermines the legitimacy of the government to provide for its people.
Keywords: Protest movements -- South Africa; Political violence -- South Africa; South Africa -- Politics and government -- 21st century; Civil rights -- South Africa; Police power -- South Africa; Abuse of administrative power -- South Africa; Police -- Complaints against -- South Africa; Right to strike -- South Africa; Democracy -- South Africa; Political leadership -- South Africa -- 21st century; Political participation -- South Africa; African National Congress; South African Police Service